2021
DOI: 10.3389/fpsyg.2021.773689
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Top Management Team Human Capital on Sustainable Business Growth

Abstract: Traditionally, enterprises have subscribed to the belief that top management team (TMT) human capital is of great influence to a specific entity. While long being a question of interest in the field of management, the extant literature rarely discusses the impact of TMT human capital on sustainable business growth. By examining data obtained from 535 TMT members of private enterprises in Zhejiang Province PRC, and investigate the mediating effect of decision-making quality as well as the moderating effect of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Finally, it is possible that other activities may also strive staff to rationalize their working time, so future research should deeply scrutiny other key activities. For example, human capital activities may be one of the other activities that may also strive staff rationalize their working time, because human capital activities also consume staff many resources to realize knowledge skills (Wang et al, 2019 ; Hu and Yao, 2021 ; Shen et al, 2021 ), such as the education training and obtaining an advanced degree.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that other activities may also strive staff to rationalize their working time, so future research should deeply scrutiny other key activities. For example, human capital activities may be one of the other activities that may also strive staff rationalize their working time, because human capital activities also consume staff many resources to realize knowledge skills (Wang et al, 2019 ; Hu and Yao, 2021 ; Shen et al, 2021 ), such as the education training and obtaining an advanced degree.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the influence of chairman's human capital cannot be ignored when studying the stability of top management team. However, recent studies mainly focus on the explicit human capital of chairman and found that the demographic differences such as gender, age, and education background will affect the management style, cohesion (Gabrielsson et al, 2007) and decision efficiency of top management team (Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%